ChemInform Abstract: Ultrasound‐Assisted Synthesis of 6‐Methyl‐1, 2, 3, 4‐tetrahydro‐N‐aryl‐2‐oxo/thio‐4‐arylpyrimidine‐5‐carboxa mides Catalyzed by Uranyl Nitrate Hexahydrate. Issue 49 (9th December 2014) - Venkatesan, K.; Satyanarayana, V. S. V.; Sivakumar, A.
Abstract The reaction can also be run under conventional heating conditions resulting in longer reaction times and slightly lower yields.